Efek Kognitif, Afektif dan Behavioral pada Kampanye Registrasi Prabayar Seluler - PRAMELANI Pramelani (Universitas Bina Sarana Informatika, 2018)
Abstract–In order to avoid criminal offenses through mobile phones, the government as of October 31, 2017 issued a requirement that all prepaid cellular cards be re-registered by sending NIK (Resident Identity Number) and family card to short message number 4444. Therefore, the government conducted a card re-registration campaign prepaid cell in various media. To find out the cognitive, affective, and behavioral effects of the campaign, the researchers distributed questionnaires to respondents who had a cell phone with the accidental sampling method. With quantitative descriptive analysis, it was found that the cognitive effect showed that the information knowledge given in the prepaid cell phone re-registration campaign was accepted by the respondents. However, the appearance of the information presented in the media is still largely considered unattractive by the respondents. And on the affective effect seen that the respondents quite happy, quite nyakin and believe in the re-registration program prepaid cellular card. Whereas in behavioral effect, respondents mostly have re-registration action of cellular card. And for those respondents who have not registered prepaid cellular card, still plan to re-register though some of them do not register their cellular card. Respondents are also quite supportive of government campaigns by providing information to others. But most of the respondents did not invite others to participate in re-registration of prepaid cellular card owned..Keywords: Campaign, Cognitive Effect, Affective Effect, Behavioral Effect, Mobile Registrastion